Improving the unit for melting cheese masses - Bondar, M.; Бондар, М. М.; Skoromna, O.; Скоромна, О. І.; Ponomarenko, Nataliia; Пономаренко, Наталія Олександрівна; Tesliuk, Hennadii; Теслюк, Геннадій Володимирович; Honcharova, I.; Гончарова, І. І.; Nedosiekova, N.; Недосєкова, Н. С.; et al. (ПП "ТЕХНОЛОГІЧНИЙ ЦЕНТР" Український державний університет залізничного транспорту, 2021)
This paper reports the improved model of the unit for melting cheese masses. The device differs in the technique of heat supply to working tanks through the replacement of a steam jacket with heating by a flexible film resistive electric heater of radiative type (FFREhRT). The heat exchange surface of the working container was increased through heating the mixing device by FFREhRT. In addition, the unit is distinguished by utilizing secondary thermal energy of melting cheese masses (35...95 °C) by converting it with Peltier elements into a low-voltage power supply to autonomous fans (3.5...12 W) in order to cool the control unit. Such a solution would improve the efficiency of the proposed structure, which is explained by reducing the dimensional and weight parameters of the cheese melting unit by replacing the steam heating technique with an electric one. A decrease in the time to enter a stationary mode (85 °C) when melting cheese masses was experimentally confirmed: for the bowl of the examined unit ‒ 575 s, compared to the analog ‒ 725 s. That confirms the reduction in the time to enter a stationary mode by 21 % compared to the base unit B6-OPE-400. The estimation has established a 1.2- time decrease in the main indicator of resource efficiency of the specific energy consumption for heating the volume of a unit of product in the improved plant for melting cheese masses – 3,037.2 kJ/kg, compared to the base B6-OPE-400 – 3,672.5 kJ/kg. The results confirm an increase in resource efficiency that is achieved by the elimination of steam heat networks; the increased heat exchange surface of working bowls by heating the stirrer with the help of FFREhRT. The heat transfer that employs FFREhRT simplifies the operational indicators of the temperature stabilization system in the bowl of the cheese mass melting unit. The results reported here may prove useful when designing thermal equipment with electric heating while using secondary thermal energy. Вдосконалено модель апарата для плавлення сирних мас, який відрізняється способом теплопідведення робочих ємностей заміною парової сорочки на обігрів гнучким плівковим резистивним електронагрівачем випромінювального типу (ГПРЕнВТ). Збільшено поверхню теплообміну робочої ємності за рахунок наявно-сті обігріву перемішуючого пристрою ГПРЕнВТ. Також апарат відрізняється наявністю використання вторинної теплової енергії плавлення сирних мас (35...95°С) перетворенням її елементами Пельтьє у низьковольтну напругу жив-лення автономних вентиляторів (3,5...12Вт) для охолодження блоку керування. Таке рішення призведедо підвищення ефективності запропонованої конструкції, що пояснюється зменшенням габаритно-вагових параметрів апарата плавлення сирних мас за рахунок заміни парового способу обігріву на електричний.Експериментально підтверджено зменшення тривалість виходу на стаціо-нарний режим (85°С) при плавленні сирних мас: для чаші дослідного апарату –575с, в порівнянні з аналогом – 725 с. Підтверджуючи про скорочення тривалос-ті виходу на стаціонарний режим на 21 % порівняно з базовим апаратом Б6-ОПЕ-400.Розрахунковим шляхом, встановлено зменшення у 1,2 рази основного пока-знику ресурсоефективності питомих витрат енергії на нагрівання об’єму оди-ниці продукту у вдосконаленому апараті для плавлення сирних мас –3037,2 кДж/кг, в порівнянні з базовим Б6-ОПЕ-400 – 3672,5 кДж/кг. Отримані результати підтверджують підвищення ресурсрефктивності, що досягаєть-ся: усуненням парових тепломереж; збільшенням поверхні теплообміну робо-чих чаш обігріванням мішалки за допомогою ГПРЕнВТ. Тепловідведення ГП-РЕнВТ спрошує експлуатаційні показники системи стабілізації температури у чаші апарата плавлення сирних мас. Отримані результати будуть корисні під час проектування теплового обладнанняз електричним обігріванням в умовах використання вторинної теплової енергії.
Удосконалення апарата для плавлення сирних масс
Keywords: cheese mass melting unit; апарат плавлення сирних мас; heat supply; теплопідведення; specific energy consumption; питомі витрати енергії; secondary energy; вторинна енергія